Influência das drogas de abuso no aumento da criminalidade na região de Pau dos Ferros/RN - Morais, Geversson Pinheiro Dias Fernandes de (Universidade Federal Rural do Semi-Árido, 2016)
Drugs represent one of the biggest problems faced by public agencies in the country, whether related to safety or health. Bringing the discussion to the city of Pau dos Ferros / RN, the objective of this study is to analyze the connection between the increase of local crime and the use of drugs of abuse based on statistical data provided by the public agencies of security and social development, as well as reflect on the point of view of local authorities on external factors that contribute to the advancement of this issue. For that, a quantitative, qualitative and comparative research was carried out, from the data collection with the Social Development Secretariat, 7th Battalion of the Military Police and 4th Regional Police Station, covering the period between the years of 2009 and the first half of 2016. Official informations show an increase in the number of cases of drug possession, theft and possession of weapons. They also show that the homicide rate increased significantly, evidencing the increase in rates of crime and violence. Faced with such factors, It´s normal to think of a possible connection between crime, violence and drug use, given that all indicators have evolved. According to local authorities, the facts that justify the advancement of this problem are strictly linked to the deficiencies of public security, since the effective police and development of security and social development policies did not follow to the satisfaction of urban expansion and growth populations experienced in Pau dos Ferros in recent years.
Keywords: Criminalidade; Drogas de abuso; Segurança pública; Crime; Drugs of abuse; Public Security; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA